2021
DOI: 10.3390/app11041483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germanium Incorporation on the Electrochemical Performance of Electrospun Fe2O3 Nanofibers-Based Anodes in Sodium-Ion Batteries

Abstract: Fe2O3 and Fe2O3:Ge nanofibers (NFs) were prepared via electrospinning and thoroughly characterized via several techniques in order to investigate the effects produced by germanium incorporation in the nanostructure and crystalline phase of the oxide. The results indicate that reference Fe2O3 NFs consist of interconnected hematite grains, whereas in Fe2O3:Ge NFs, constituted by finer and elongated nanostructures developing mainly along their axis, an amorphous component coexists with the dominant α-Fe2O3 and γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Araujo and co-researchers reported the avarage fiber diameter of electrospun Fe 2 O 3 was 360 nm with a diameter distribution ranging from 200 to 900 nm, calcinated at 800 C using Iron (III) nitrate nonahydrate and polyvinylpyrrolidone [65]. Another work executed by Petrovicovà and coworkers reported that the diameters of hematite fibers calcined for 2 h at 600 C varied between 120 and 500 nm using iron (II) acetate and polyacrylonitrile (PAN) as precursors [66]. In that study, the smaller average diameter of hematite fibers could be fabricated at a lower calcination temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Araujo and co-researchers reported the avarage fiber diameter of electrospun Fe 2 O 3 was 360 nm with a diameter distribution ranging from 200 to 900 nm, calcinated at 800 C using Iron (III) nitrate nonahydrate and polyvinylpyrrolidone [65]. Another work executed by Petrovicovà and coworkers reported that the diameters of hematite fibers calcined for 2 h at 600 C varied between 120 and 500 nm using iron (II) acetate and polyacrylonitrile (PAN) as precursors [66]. In that study, the smaller average diameter of hematite fibers could be fabricated at a lower calcination temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, carbon nanofibers with fine fiber diameters additionally improve the active sites in the electrode structure. The nano-sized active materials on carbon nanofibers increase the ion transport rates in rechargeable batteries [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, enormous efforts have been made to improve its electrical conductivity, including foreign-ion doping or forming heterojunctions with other materials to enhance charge separation and transfer. 22,23 Metal ion doping in the α-Fe 2 O 3 lattice (such as Sn, 24 Ti, 25 Si, 26 Pt, 27 Zr, 28 Ge, 29 Cr, 30 and Zn 31 ) is found to be an effective method to improve its bulk transport property. Among various dopants, Sn 4+ doping by surface treatment and by self-Sn diffusion from an underlying fluorine doped SnO 2 (FTO) substrate has attracted great attention because Sn ion is subtly different in ionic radius and Pauling electronegativity compared to Fe ion.…”
Section: Introductionmentioning
confidence: 99%